Comparative study of geomorphological and sedimentological characteristics of Tigani and Mikali coastal zones (SE Samos) - Bleta, A.; Evelpidou, N.; Andris, P.; Karditsa, A.; Markakis, E.; Poulos, S. (Bulletin of the Geological Society of Greece, 2008)
The present study investigates the principal morphological and sedimentological (textural) characteristics of the beach-zones along the Tigani and Mikalis Bays, which are located at the southeastern coast of Samos Island. It is also examined their retreat due to the expected sea level rise induced by the climatic change. The beach zones under investigation has been formed in front of alluvial coastal plains, while at their western end host the mouth of small (ephemeral) rivers. Their width varies between 12 and 25 m, becoming narrower towards their eastern ends; this shows that the longshore sediment transport, which is from W to E due to their coastline orientation relatively to incoming waves, has not been strong enough to move most of the sediment eastwards. The subaerial part of both beach zones consists of gravels, while their subaqueous part is covered by sand. The presence of low dunes at the backshore odf the Thiogani Bay in association with the lack of sand between the dunes and the shoreface indicate that the beach zone is under erosion. Furthermore, with respect to the expected sea-level rise the shoreline of Tigani bay may be retreat by 15-20 m, when the nearby shoreline of Mikalis bay could retreat 12-15 m.